OBSERVATIONS ON THE BIOLOGY OF CUTTLEFISH SEPIELLA INERMIS AT MANDAPAM - Unnithan, K Asokakumaran (Indian Journal of Fisheries, 2011)
Sepiella inermis was found to grow to a size of 50 mm at the end of first year and 80 mm of mantle length at the end of second year. The size at first sexual maturity is 50 mm for males and 31 mm for females. Prawns were the main item of food of the species